Optimización de la gestión del proceso de planeación de pozos de Equión Energía mediante la utilización de la herramienta Daptiv PPM (2018)
In this graduation project, the management of the well planning process of Equion Energia was optimized through the use of Daptiv PPM. In order to achieve this, a multidisciplinary project was done. It included the identification of the key data and critical indicators of the company's well planning process; the respective data modelling using Daptiv PPM; the generation of a methodology to use Daptiv PPM as the project management tool of the company's well planning process and the implementation of the methodology. All previously said allowed to integrate in one tool the planning information of the drilling and completion projects, simpliflying the visibility, track and control of the information of this type of projects; facilitating the collaboration and communication between teams.